Synthesis and Biological Activity of Ni(II), La(III), and Ce(IV) Complexes with 8-Hydroxy-7-iodo-6-((4-sulfophenyl)diazinyl)quinoline-5-sulfonic Acid Ligand - Muhi, Noora Qasem; Abbas, Alyaa Khider (Universitas Gadjah Mada, 2026)
In this study, a new azo ligand, 8-hydroxy-7-iodo-6-((4-sulfophenyl)diazinyl)quinoline-5-sulfonic acid (HAQ), was synthesized from 8-hydroxy-7-iodo-quinoline-5-sulfonic acid using a diazotization-coupling procedure and then complexed with La(III), Ni(II), and Ce(IV) ions. The ligand and its metal complexes were analyzed using elemental analysis, FTIR, UV-vis, 1H-NMR, TGA, SEM, ICP, and XRD techniques. Spectral and analytical results indicated the effective coordination of oxygen and nitrogen donor atoms, resulting in stable 1:1 (metal:ligand) of [La(HAQ)Cl2(H2O)2]·5H2O, and (1:2) of [Ce(HAQ)2(SO4)]·H2O and [Ni(HAQ)2(H2O)2]·4H2O complexes. Thermal analysis has revealed that metal complexes are more thermally stable than their corresponding free ligands. SEM showed significant morphological modifications during complexation, whereas XRD patterns revealed an increase in crystallinity in the metal complexes. The antioxidant characteristics of the synthesized compounds were evaluated using the phosphomolybdate technique, with the Ce(IV) complex displaying the highest activity, most likely due to its redox capacity. Overall, the results highlight the potential of HAQ and its metal complexes as promising candidates for antioxidant and anticancer applications. These findings warrant further mechanistic studies and in vivo evaluations.